Gaining Traction or Spinning Wheels? : Factors Influencing the Effectiveness of Grievance Mechanisms in World Bank-Financed Projects - World Bank (Washington, DC : World Bank, 2022)
This paper explores which factors influence the success of a GM and under what circumstances GMs trigger, or fail to trigger, improvements in project design, changes in power dynamics, or community relations. By doing so, it aims to produce clearer insights into the roadblocks as well as the dynamics of positive change achieved through GMs (Aslam, Grandvoinnet, and Raha 2015: 70). Although the World Bank offers several avenues for grievance redress to project beneficiaries, this paper focuses on project-level GMs in IPF, which are the responsibility of the World Bank’s clients, that is, public sector agencies and ministries. The key research question explored is: What factors influence the effectiveness of project-level GMs? This paper relies on a mixed-methods approach. Fifteen qualitative, semi-structured interviews were conducted over a six-week period in February and March 2020 by the author with World Bank practitioners specializing in social safeguards policies and the supervision of social aspects, including GM implementation, in World Bank-financed projects. In April 2020, an online survey of 94 GM focal points in implementing agencies was conducted in 24 countries; its 23 questions probed the design, track record, strengths, and weaknesses of project-level GMs (World Bank 2021a). Follow-up discussions were then held with eight project implementation unit (PIU) members from two projects. Finally, the paper also relies on extensive case study analysis.